2021
DOI: 10.3390/en15010195
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Structure Revealing a Likely Mud Volcano off the Dongsha Island, the Northern South China Sea

Abstract: The Dongsha Island (DS) is located in the mid-northern South China Sea continental margin. The waters around it are underlain by the Chaoshan Depression, a relict Mesozoic sedimentary basin, blanketed by thin Cenozoic sediments but populated with numerous submarine hills with yet less-known nature. A large hill, H110, 300 m high, 10 km wide, appearing in the southeast to the Dongsha Island, is crossed by an ocean bottom seismic and multiple channel seismic surveying lines. The first arrival tomography, using o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Some of phenomenon of oil-gas leakage is indirect evidence, such as mud volcanoes and hydrates [3], [12], it can be observed that the acid-extraction hydrocarbon methane is abnormally developed in the seafloor sediment above the reservoir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of phenomenon of oil-gas leakage is indirect evidence, such as mud volcanoes and hydrates [3], [12], it can be observed that the acid-extraction hydrocarbon methane is abnormally developed in the seafloor sediment above the reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…It is divided into 6 secondary tectonic units (Figure 1), namely eastern sag, western sag, northern slope, middle slope, western slope, and middle low uplift, with an overall NNE direction distribution. Well LF35-1-1 has revealed organic-rich Middle to Upper Jurassic strata [1], indicating good hydrocarbon generation potential and the conditions for the formation of various types of oil-gas reservoirs [2][3][4][5][6][7][8][9][10][11][12][13][14]. However, due to multiple tectonic events, strong uplift and erosion have occurred, resulting in the development of fault structures.…”
Section: Introductionmentioning
confidence: 99%
“…The Dongsha Sea is an area in the northeast of the South China Sea comprising of thick Mesozoic strata, and the Chaoshan Depression is the largest residual depression in the area (Figure 1). The depression has undergone six stages of tectonic evolution in the Mesozoic and Cenozoic eras: (1) In the late Triassic rifting period, semi enclosed bay began to develop in the Mesozoic basin in the northeast of South China Sea; (2) During the Jurassic depression period, the largest scale transgression occurred, and the basin expanded to its maximum extent; (3) In the Late Jurassic tectonic uplift period, compaction fold and structural unconformity occurred under compression; (4) In the Early Cretaceous re-subsidence period, volcanic debris, lava flows, and continental margin debris began to rapidly fill and deposit in the basin; (5) In the Late Cretaceous tectonic inversion period, under the influence of four episodes of the Yanshan movement, the Chaoshan Depression was uplifted and denuded again, forming the second regional unconformity; and (6) In the Neogene regional thermal subsidence period, the central basin of the South China Sea reached its peak of expansion during the Miocene, and the Cenozoic basins in the northern continental margin of the South China Sea successively entered a stage of post-rift depression evolution; large-scale transgression also occurred, mainly accepting coastal and shallow marine deposits [33][34][35][36][37][38]. The DS-A structure is located in the M-low bulge and is a fault anticline structure (Figure 1), controlled by NE-, NNE-, and NW-trending faults.…”
Section: Geological Settingmentioning
confidence: 99%
“…Yan et al ( 2021) [8] used ocean bottom seismic data to perform first-arrival tomography, which showed two obvious phenomena: (1) a low-velocity (3.3 to 4 km/s) zone with a size of 20 × 3 km 2 (centering at ~4.5 km depth) and ( 2) an underlying high-velocity (5.5 to 6.3 km/s) zone of comparable size at ~7 km depth. MCS profiles showed highly fragmented Cenozoic sequences that covered a wide chaotic reflection zone within the Mesozoic strata below hill H110.…”
Section: Special Issue Contentmentioning
confidence: 99%